2006
DOI: 10.1093/jn/136.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Inhibits Liver Growth during Refeeding in Rats via Control of Ribosomal Protein Translation but Not Cap-Dependent Translation Initiation

Abstract: We examined the role of the mammalian target of rapamycin (mTOR) in hepatic cell growth. To dissociate cell growth from cell proliferation, we employed an in vivo model of nonproliferative liver growth in rats, refeeding after 48 h of food deprivation. Starvation resulted in a decrease in liver mass, liver protein, and cell size, all of which were largely restored after 24 h of refeeding. Administration of the mTOR inhibitor, rapamycin, before the refeeding period partially inhibited the restoration of liver p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 37 publications
3
37
0
Order By: Relevance
“…This increase might induce activation of the mTOR signaling pathway. As in the previous study (22), phosphorylation of S6 was increased in fasted rats compared with fed rats (data not shown). However, the level of PTB in the cytoplasmic fraction is increased in fasted rats.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This increase might induce activation of the mTOR signaling pathway. As in the previous study (22), phosphorylation of S6 was increased in fasted rats compared with fed rats (data not shown). However, the level of PTB in the cytoplasmic fraction is increased in fasted rats.…”
Section: Discussionsupporting
confidence: 87%
“…The mRNAs encoding most ribosomal proteins contain a 5 ¢ -TOP sequence ( 23 ). Rapamycin treatment before a refeeding for 24 h clearly inhibited recruitment of ribosomal protein mRNA into polysomes ( 22 ). On the other hand, the results of microarray analysis showed that 78 different mRNAs had increased polysome association after feeding in the liver (21).…”
Section: Discussionmentioning
confidence: 99%
“…1S). These findings are consistent with the work of Anand and Gruppuso (55), which show that formation of the eIF4G⅐eIF4E complex during refeeding is rapamycin-resistant; i.e. is not dependent on signaling via mTOR.…”
Section: Asparagine Depletion Induces Expression Of Asparagine Synthesupporting
confidence: 92%
“…B: hierarchy of fold-differences between the two groups. An inflection point calculated using these data was a log2 ratio of 1, corresponding to a fold difference of 2. regulator of translation initiation that is responsive to amino acid restriction (3,59). To assess these two signaling pathways, we analyzed fetal liver homogenates from control and IUGR fetuses by phospho-specific Western immunoblotting.…”
Section: Resultsmentioning
confidence: 99%